2014
DOI: 10.1016/j.indmarman.2014.06.015
|View full text |Cite
|
Sign up to set email alerts
|

When do they care to share? How manufacturers make contracted service partners share knowledge

Abstract: Manufacturing firms that outsource customer-facing services, risk losing touch with their customers and thereby forfeit valuable market and customer-related knowledge. To maintain informed and competitive, the manufacturer's customer-facing service partners should engage in knowledge sharing and transfer their market knowledge and insight to the firm. Building on knowledge transfer and organizational learning theory, this study investigates how contractual and non-contractual (i.e., relationship) characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 100 publications
0
16
0
Order By: Relevance
“…In this study, we adopt a relationship focus on outsourcing, which can be considered as a complementary approach to the strategic view, addressing how to manage the outsourcing relationship after the decision to outsource has been made. Prior research on the management of the outsourcing relationship has studied, for example, practices for managing the relationship in different contexts (e.g., Baraldi et al, 2014;Levina & Vast, 2008;de Vries et al, 2014; see Appendix 1). Overall, this stream of research concludes that the management of the outsourcing relationship, including integration, is critical for successful outsourcing (e.g., Boulaksil & Fransoo, 2010;Harmanciouglu, 2009;Narasimhan et al, 2010).…”
Section: Research On Outsourcingmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we adopt a relationship focus on outsourcing, which can be considered as a complementary approach to the strategic view, addressing how to manage the outsourcing relationship after the decision to outsource has been made. Prior research on the management of the outsourcing relationship has studied, for example, practices for managing the relationship in different contexts (e.g., Baraldi et al, 2014;Levina & Vast, 2008;de Vries et al, 2014; see Appendix 1). Overall, this stream of research concludes that the management of the outsourcing relationship, including integration, is critical for successful outsourcing (e.g., Boulaksil & Fransoo, 2010;Harmanciouglu, 2009;Narasimhan et al, 2010).…”
Section: Research On Outsourcingmentioning
confidence: 99%
“…The study contributes to the research on outsourcing by developing an understanding of the management of the outsourcing relationship in the operations context by illustrating how it depends on the operational strategic priority related to the specific object of outsourcing (Boulaksil & Fransoo, 2010;Handley & Benton, 2009Ishizaka & Blakiston, 2012;Narasimhan et al, 2010;Ndubisi, 2011;de Vries et al, 2014). Moreover, the study contributes to research on more generic buyer-supplier relationships by developing a contextualized understanding of the management of buyer-supplier relationships (e.g.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…First, structural governance refers to the design phase where the basis of the governance structure is defined (Steinicke, Wallenburg, and Schmoltzi, 2012). The effects of structural governance elements, such as contractual incentives and specification level (De Vries, Schepers, van Weele, and van der Valk, 2014), the number of contractual clauses (Reuer and Ariño, 2007), contractual functions such as coordinating or safeguarding (Hofman et al, 2017), and ownership models such as equity-and non-equity-based relationships (Murray and Kotabe, 2005) have been extensively evaluated in past works.…”
Section: Randd Project Formalizationmentioning
confidence: 99%
“…Relational governance is indispensable in alliance cooperation. De Vries et al [37] found that good relationship quality and cooperation experience can enhance the relationship strength between partners and that the relationship strength positively affects the development of exploitative and exploratory cooperation.…”
Section: The Alliance Portfolio Management Capabilitymentioning
confidence: 99%